Evaluasi Pembelajaran Sejarah dalam Kurikulum Merdeka Belajar : Studi Kasus di SMA Negeri 2 Sukoharjo - Athanasius Agung Budi Aprilianto; Leo Agung Sutimin (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to evaluate the planning, implementation, and challenges of history education in the implementation of the Merdeka Belajar Curriculum at Sukoharjo State Senior High School 2, as well as to contribute to the advancement of knowledge, particularly in the fields of history education and curriculum evaluation. This study is motivated by the importance of implementing the Merdeka Belajar Curriculum in improving the quality of history education, which is oriented not only toward knowledge acquisition but also toward the development of students’ character, competencies, and critical thinking skills in accordance with national educational goals.The research method used was qualitative descriptive to describe the phenomenon in depth. Data collection was conducted through interviews, classroom observations, and document analysis, while data validity was tested using source triangulation to ensure the accuracy and credibility of the research. The research findings indicate that instructional planning is developed through Teaching Modules, Learning Objective Sequences (ATP), and Learning Outcomes (CP) that are integrated with the Pancasila Student Profile. The implementation of instruction encourages student engagement through discussions and group work to develop critical thinking skills, independence, and cooperation. The main challenges faced include limited instructional time and variations in student participation.